1985
DOI: 10.1136/bmj.290.6485.1866
|View full text |Cite
|
Sign up to set email alerts
|

Honey in the treatment of infantile gastroenteritis.

Abstract: A clinical study was undertaken using honey in oral rehydration solution in infants and children with gastroenteritis. The aim was to evaluate the influence of honey on the duration of acute diarrhoea and its value as a glucose substitute in oral rehydration. The results showed that honey shortens the duration of bacterial diarrhoea, does not prolong the duration of non-bacterial diarrhoea, and may safely be used as a substitute for glucose in an oral rehydration solution containing electrolytes. The correct d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
3

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 11 publications
2
59
0
3
Order By: Relevance
“…A clinical study of honey treatment in infantile gastroenteritis was reported by Haffejee & Moosa [62] and Abdelrahman et al [63], they found that honey shorten the duration of diarrhoea in patients with bacterial gastroenteritis caused by organisms such as Salmonella, Shigella and E. coli. They recommended that honey was a safe substitute for glucose as long as it provided 111 mmol/l each of glucose and fructose.…”
Section: Gastroenteritismentioning
confidence: 99%
“…A clinical study of honey treatment in infantile gastroenteritis was reported by Haffejee & Moosa [62] and Abdelrahman et al [63], they found that honey shorten the duration of diarrhoea in patients with bacterial gastroenteritis caused by organisms such as Salmonella, Shigella and E. coli. They recommended that honey was a safe substitute for glucose as long as it provided 111 mmol/l each of glucose and fructose.…”
Section: Gastroenteritismentioning
confidence: 99%
“…Honey given at a concentration of5 % (v Iv) in place of glucose in a rehydration fluid was found to give a statistically significant reduction in the duration of bacterial diarrhea (58 versus 93 h), and give no increase in the duration of nonbacterial diarrhea in a clinical trial conducted on infants and children admitted into hospital with gastroenteritis [119]. In a clinical trial in which 4S patients with dyspepsia were given no medication other than honey substantial reductions were found to result in the number of patients passing blood (from peptic ulcers) in their feces, the number with dyspepsia and the number with gastritis, duodenitis or a duodenal ulcer seen on endoscopy [120].…”
Section: Clinical Evidence For Effectiveness Of Honey On Infected Woumentioning
confidence: 99%
“…It was concluded that honey can be safely used as substitute of glucose in oral rehydration solution provided it contains electrolytes in recommended amounts. 17 …”
Section: Anti-diarrheal Activitymentioning
confidence: 99%